Situated Affects and Place Memory. - Sutton, John (Topoi: An International Review of Philosophy, 2024)
Traces of many past events are often layered or superposed, in brain, body, and world alike. This often poses challenges for individuals and groups, both in accessing specific past events and in regulating or managing coexisting emotions or attitudes. We sometimes struggle, for example, to find appropriate modes of engagement with places with complex and difficult pasts. More generally, there can appear to be a tension between what we know about the highly constructive nature of remembering, whether it is drawing on neural or worldly resources or both, and the ways that we need and use memory to make claims on the past, and to maintain some appropriate causal connections to past events. I assess the current state of work on situated affect and distributed memory, and the recent criticisms of the 'dogma of harmony' in these fields. I then deploy these frameworks to examine some affective dimensions of place memory, sketching a strongly distributed conception of places as sometimes partly constituting the processes and activities of feeling and remembering. These approaches also offer useful perspectives on the problems of how to engage – politically and aesthetically – with difficult pasts and historically burdened heritage. In assessing artistic interventions in troubled places, we can seek responsibly to do justice to the past while fully embracing the dynamic and contested constructedness of our present emotions, memories, and activities.